Murmansk Arctic State University – Institution with the Northern Character - Andrey M. Sergeev; Irina M. Shadrina; Vladislav V. Gromov (Высшее образование в России)
The article focuses on the issues of the formation of a conceptually new target model of a regional flagship university. Based on the experience of the formation and development of the Murmansk Arctic State University, which acquired the status of a flagship one in 2017, the authors analyze the origins of the formation of the model, its specificity, which is substantively and formally defined in the parameters of the Arctic perspective. The major intensively developing areas of MASU’s activity in the past two years have been focuses on two important factors of regional development, implemented in the form of two strategic flagship university projects. The first strategic project – “MASU is the scientific and technological hub of the region” – is aimed at solving the most acute regional task of effectively using both the economic and scientific / innovative potential of the region. The second strategic project – “Creative City is a Territory of Development” – reflects the interaction of the creative communities of the region, the Russian Federation and the world with prospect consumers represented by the regional government, municipalities, institutions and industrial enterprises. MASU is the main platform for combining a variety of strategies and searches aimed at changing urban and township sociocultural spaces, an integrator of various areas of design, creative technologies and cultural practices that affect the improvement of the quality of life and human capital development. The key role is determined by the role of the flagship university as a driver of the regional socio-economic development. The developing dialogue between the university, business and government is affirmed as an indispensable condition for the University’s successful functioning and a pledge for its further development.